Survey On Competence and Administration of Supervisory Board Activities in German Stock-Listed Companies - Michelberger Knut J. (Economics and Business)
According to the agency theory (Jensen & Meckling 1976), it is expected that there exists a positive relationship between corporate governance and company performance which is also generally assumed in recent research (Dignam & Galanis 2016). This relationship is investigated in the study performed by the author of this paper. Two different approaches were chosen in parallel: (1) quantitative data analysis, based on financial figures and corporate governance variables, and (2) a survey of supervisory board members of listed German companies. This paper is about the results of structured interviews with 30 supervisory board members. The survey confirms that corporate governance regulations have an important influence on the administration of supervisory board activities and on board competence. Many supervisory board members stated that the German Corporate Governance Codex leads to extended meeting time to fulfil regulatory requirements, more data requirements to identify and estimate risk issues and to rising risk awareness. The interview results converge with the results from the multivariate analysis.